2014
DOI: 10.1016/j.jceh.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Virological Response Rates to Antiviral Therapy in Genotype 1 and 3 Chronic Hepatitis C Patients: A Study from North India

Abstract: Background: In India, both genotype 3 and 1 are predominant genotypes in patients with chronic hepatitis C (CHC). However, there is scanty data on sustained viral response (SVR) rate with conventionally recommended dual therapy with PEG-IFN and ribavirin. Methods: In this retrospective study, consecutive patients of CHC of genotypes 1 and 3, attending the single unit of Gastroenterology of our hospital, who received PEG-IFN and ribavirin therapy, were included. Patients who had co-infection with HIV or HBV wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…On the other hand, ALT levels were not significantly associated with SVR. This is in agreement to previous studies which also demonstrated lack of prognostic value of ALT levels with ETR in CHC patients of genotype 3 and 1 45 46 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, ALT levels were not significantly associated with SVR. This is in agreement to previous studies which also demonstrated lack of prognostic value of ALT levels with ETR in CHC patients of genotype 3 and 1 45 46 .…”
Section: Discussionsupporting
confidence: 93%
“…As per the American Association for the Study of Liver Diseases guidelines PCR-positive patients at the end of treatment and three months after the completion of treatment were stated as non-responders [13]. Patients who were negative by PCR at the end of treatment at 12 weeks but were found to be positive by PCR at three months after the end of treatment were labeled as relapsed.…”
Section: Definitions and Interventionmentioning
confidence: 99%
“…The most prevalent HCV genotype in India is genotype 3, and the standard therapy for this genotype till now had been a combination of PEG-IFN and RBV for 24 wk, with an SVR rate of 70 per cent or more 7 . The SVR rate for those infected with genotype 1 (the second most common HCV genotype in India) was 40-60 per cent, with a treatment duration of 48 wk 12 13 14 . Traditionally, HCV-genotypes 2 and 3 were considered to be easy to treat and 1 and 4 were considered to be difficult to treat with conventional PEG-IFN–RBV therapy 12 .…”
Section: Evolution Of Hepatitis C Virus (Hcv) Treatmentmentioning
confidence: 99%
“…Undetectable HCV RNA at week four of therapy, also known as the rapid virologic response (RVR), is one of the strongest predictors of SVR 14 39 . Thus, a shorter duration of treatment of 24 wk of PEG-IFN plus RBV dual therapy can be given to patients who do not achieve an RVR 40 .…”
Section: Recommendations Of Indian National Association For Study Of mentioning
confidence: 99%